A Uniform Choice of Law Rule for the Taking of Collateral Interests in Securities : Using Private Law Approaches to Reduce Credit and Legal Risk in Financial Systems.: Using Private Law Approaches to Reduce Credit and Legal Risk in Financial Systems. (2001) - Unknown
No abstract available